Interaction between afternoon aeration and tilapia stocking density - Francisco Roberto dos Santos Lima; Davi de Holanda Cavalcante; Vanessa Tomaz Rebouças; Marcelo Vinícius do Carmo e Sá (Acta Scientiarum. Animal Sciences, 2016)
The present study aimed at determining the effects of the interaction between afternoon aeration and stocking density of Nile tilapia on variables of water and soil quality, growth performance and effluent quality. The experiment was a 3 x 2 factorial randomized block design, with three stocking densities (8, 12 and 16 fish per tank or 43.5, 65.3, and 87.0 g m-3) under two mechanical aeration regimes, absence (control; three replicates) and afternoon aeration (four replicates). The afternoon aeration was carried out from 12.00 a.m. up to 18.00 p.m. from the 3rd week until the end of the experiment. Except for the 16-fish tanks, the lowest concentrations of total ammonia nitrogen were found in the tanks with higher density of fish provided with afternoon aeration. Nitrite concentrations were lower in the 8-fish aerated tanks. In intensive system, the afternoon aeration of the fish culture water is an efficient management of water quality to remove gaseous ammonia and nitrite from water, but it is not appropriate to remove hydrogen sulfide from water.